Precision machining VII : selected, peer reviewed papers from the 7th International Congress of Precision Machining (ICPM 2013), October 3-5, 2013, Miskolc, Hungary - Kundrák, János; Maros, Zsolt (Key engineering materials ;, 2014)
This collection of papers provides the most up-to-date information available for researchers and engineers who are interested in any aspect of the field of precision machining. The book includes papers from fields of precision machining and processes as well as related topics such as tools, methods, quality assurance and logistics. The major goal is to search for methods for providing increased endurance and reliability of products at reduced production and assembly cost. The contents are presented under the headings of: I. Cutting Tools; II. Machining Processes; III. Hard Machining; IV. Abras.